2018
DOI: 10.1007/s10948-018-4821-6
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Dynamic Phases in Type II Superconducting Strips with Regular and Flattened Triangular Pinning Arrays

Abstract: The dynamic behavior of vortices in type II superconducting infinite strips is simulated with two types of triangular pinning lattices: the regular one and a flattened triangular array that mimics the vortex lattice in a superconducting strip in the absence of a pinning array. The calculations were made at zero temperature and perpendicular magnetic field. The size effects are investigated for several strip widths maintaining the density and size of pinning centers unchanged. A driving force is applied in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Other aspects have also been explored such as adding asymmetry to the arrays [21], introducing local heating in order to produce both S-shaped and N-shaped velocity-force curves in analogy to those found in conduction curves for semiconductors [22], and inducing density wave propagation [23]. Numerous other studies of superconducting vortices in periodic pinning arrays have revealed multiple depinning transitions, the flow of interstitials, kink flow, and multiple step jumps in the velocity-force curves [24,25,26,27,28,29,30,31,32] Previous studies involved strictly overdamped particles; however, non-dissipative forces can also arise, such as the Magnus gyrotropic force [33,34], which creates a velocity component perpendicular to the forces acting on the particle [33,35]. In superconducting vortex systems, Magnus forces are possible, and experiments have found evidence for transverse motion or the vortex Hall effect [36], with more recent observations showing vortex Hall angles of up to 45 • in certain types of superconducting systems [37].…”
Section: Introductionmentioning
confidence: 99%
“…Other aspects have also been explored such as adding asymmetry to the arrays [21], introducing local heating in order to produce both S-shaped and N-shaped velocity-force curves in analogy to those found in conduction curves for semiconductors [22], and inducing density wave propagation [23]. Numerous other studies of superconducting vortices in periodic pinning arrays have revealed multiple depinning transitions, the flow of interstitials, kink flow, and multiple step jumps in the velocity-force curves [24,25,26,27,28,29,30,31,32] Previous studies involved strictly overdamped particles; however, non-dissipative forces can also arise, such as the Magnus gyrotropic force [33,34], which creates a velocity component perpendicular to the forces acting on the particle [33,35]. In superconducting vortex systems, Magnus forces are possible, and experiments have found evidence for transverse motion or the vortex Hall effect [36], with more recent observations showing vortex Hall angles of up to 45 • in certain types of superconducting systems [37].…”
Section: Introductionmentioning
confidence: 99%